Social geomatics: participatory forest mapping to mediate resource conflict in the Bolivian Amazon - Cronkleton, P.; Albornoz, M.A.; Barnes, G.; Evans, K.; Jong, W. de (2010)
This paper describes a participatory mapping method field tested with agro-extractive settlements in the Bolivian Amazon. A regional transition from customary to formal property rights resulting from sweeping 1996 land tenure reforms has led to confusion and conflicts over resource rights, a problem compounded by recent high market prices for Brazil nuts. In response to community requests to clarify resource rights to Brazil nut trees, CIFOR offered to train community members to map trees, trails and other key features themselves. This experience indicates that local residents can map their resources in an effective and efficient way and in the process gather necessary information to mediate competing claims, demonstrate their legitimate resource claims to external stakeholders and make management decisions. We argue that maps and properties are more likely to be seen as legitimate reflections of de facto rights if local stakeholders are involved as a group from the outset